Do harbour porpoises target offshore installations as feeding stations? - V.L.G. Todd; Paul Lepper; I.B. Todd (2007)
Two sets of field trials were performed from offshore installations in the German Entenschnabel sector of the Dogger Bank, North Sea. Trial 1 was undertaken from the jackup drilling rig Noble Kolskaya and its support vessel Northern Seeker, at locations B4-5 and B11-4 over three discrete periods (October/November 2004 and December 2004/January 2005). The purpose of these trials was to perform measurements of acoustic noise levels generated by the rig during routine activities and to undertake preliminary passive acoustic monitoring (using T-PODs) of porpoises (Cetacea: Phocoena phocoena) around the rig. Trial 2 was a six-month study (August 2005-January 2006) using T-PODS around the A6-A gas-production platform when it was isolated, when the Noble Kolskaya was docked alongside, and after the rig’s departure. Sound levels generated by the Kolskaya were similar to previous measurements from metal-legged bottom-founded platforms, both in level (120 dB re 1μPa) and in the frequency range of dominant tonals (2-1400 Hz). Sound levels were highly variable over short periods, shifting 15-20 dB between quietest (holding) and loudest (drilling) operations. The rig was significantly quieter than its associated support vessels; rig high frequency sound levels dropped rapidly > 8 kHz. With the exception of rig-docking/rig-departure manoeuvres, porpoise activity appeared to be independent of platform/rig activity. The greatest porpoise activity was observed during the winter months; porpoise activity and feeding rates were significantly reduced in periods of heavy weather. Here we present data to suggest that harbour porpoises may be using installations in the Dogger Bank on a seasonal basis and that installations may enhance porpoise habitat by acting as artificial reefs and feeding stations, especially during the winter months. However, these are preliminary snapshot findings. To answer completely the question posed in the title of this paper, we would need to undertake baseline and controlled and replicated longer-term ...